SaaS Business Process Management for projects seeking grants in a university context - Saboya Rios, Nemias (2018)
BPM is a methodology that is focused mainly on process management, rather than on its results; compared to others such as total quality management (TQM), Lean, Six sigma among others. The purpose of the research study was to develop a process model to improve the management of research projects competing for internal grants in a university context with the Business Process Management SaaS approach. The type of research applied was a quantitative and technological approach because it was proposed to formalize the process supported with an application in the cloud under the BPM SaaS approach. For the development of the research project, the tools of the Bizagi Studio suite were used to design the processes and for the comparison of the results, and an instrument was developed that was validated by experts and applied to representatives of teachers, administrators and students. The results showed that the process to manage the research projects effectively fulfill the established requirements, such that the statistical results corroborate that 60% and 100% of those that validated the process indicated that the modeling and design are in Excellent level and 90% of them said that the monitoring and execution of the process are at the same level. The study showed that the design, modeling, control and execution of the proposed process based on BPM SaaS managed to contribute to the management of research projects internal competitions